Role of Phosphatidylinositol 3-Kinase (PI3K), Mitogen-Activated Protein Kinase (MAPK), and Protein Kinase C (PKC) in Calcium Signaling Pathways Linked to the α1-Adrenoceptor in Resistance Arteries - Gutiérrez, Alejandro; Contreras, Cristina; Sánchez, Ana; Prieto, Dolores (Frontiers in Physiology, 2019)
Imbalance between insulin vascular actions via the phosphatidylinositol 3-Kinase (PI3K) and the mitogen activated protein kinase (MAPK) signaling pathways in insulin resistant states results in endothelial dysfunction and abnormal vasoconstriction. The role of PI3K, MAPK and protein kinase C (PKC) in Ca2+ handling of resistance arteries involved in arterial pressure regulation, is poorly understood. Therefore, we assessed here whether PI3K, ERK-MAPK and PKC play a role in Ca2+ signaling pathways linked to adrenergic vasoconstriction in resistance arteries. Simultaneous measurements of [Ca2+]i in vascular smooth muscle (VSM) and tension were performed by Fura-2M ratiofluorometry in endothelium-denuded 3rd order branches of the mesenteric artery from Wistar rats mounted in microvascular myographs. Responses to CaCl2 readmission were assessed in arteries kept in Ca2+-free medium and activated with phenylephrine (PE), in the absence and presence of the antagonist of voltage-dependent L-type Ca2+ channels nifedipine, cyclopiazonic acid (CPA) to block sarcoplasmic reticulum (SR) intracellular Ca2+ release or specific inhibitors of PI3K, ERK-MAPK or PKC. Activation of α1-adrenoceptors with PE stimulated both intracellular Ca2+ mobilization and Ca2+ entry along with contraction in resistance arteries. Both [Ca2+]i and contractile responses were inhibited by nifedipine while CPA abolished intracellular Ca2+ mobilization and modestly reduced Ca2+ entry. Inhibition of the ERK-MAPK did not alter intracellular Ca2+ mobilization but largely reduced L-type Ca2+ entry elicited by PE without altering vasoconstriction. The PI3K inhibitor LY-294002 moderately reduced intracellular Ca2+ release, Ca2+ entry and contraction induced by the α1-adrenoceptor agonist, while PKC inhibition decreased PE-elicited Ca2+ entry and to a lesser extent contraction without affecting intracellular Ca2+ mobilization. All 3 kinase inhibitors significantly reduced [Ca2+]i increase elicited by high K+ depolarization independently of yanodine receptor (RyR)) supporting a role in the activation of L-type Ca2+ entry in VSM. In summary, our results demonstrate that PI3K, ERK-MAPK and PKC regulate Ca2+ handling coupled to the α1-adrenoceptor in VSM of resistance arteries and related to both contractile and non-contractile functions. These kinases represent potential pharmacological targets in pathologies associated to vascular dysfunction and abnormal Ca2+ handling such as obesity, hypertension and diabetes mellitus, in which these signaling pathways are profoundly impaired.